Reticulocyte hemoglobin and its importance in early diagnosis of iron deficiency anemia - Márquez-Benítez, Yusselfy; Cruz-Rubio, Shirley Gigiola; Vargas-Acevedo, Diana Marcela (Universidad y Salud, 2018)
Introduction: The reticulocyte hemoglobin content (CHr) is a parameter in automated hematological biometrics, which can provide information on the iron content. So it has been used as a marker of the bioavailability of iron in the erythropoiesis, it allows its detection at an early stage of iron deficiency anemia and other pathologies such as chronic inflammation, chronic kidney disease; in addition to monitoring therapy with erythropoietin and iron. Objective: To expose the applicability of CHr as a parameter in the early diagnosis of iron deficiency anemia, as well as its measurement and interpretation. Materials and methods: The review of scientific articles in English and Spanish was carried out in the PubMed, ScienceDirect, LILACS and Medline databases, using descriptors validated in Medical Subject Headings (MeSH), considering the publication period of 80% less than 5 years. Results: The importance, applicability, determination and interpretation of this parameter is described as an early specific biomarker in the blood in the diagnosis of iron deficiency before presenting morphological changes occurring during terminal erythroid differentiation. Conclusions: CHr is a very useful parameter in the early diagnosis of iron deficiency anemia and other pathologies such as functional deficiency, chronic inflammation states and chronic renal disease